DAILY BLOOD PRESSURE PATTERN DISORDERS IN PATIENTS WITH STAGE II ESSENTIAL HYPERTENSION AND FREQUENT PREMATURE BEATS - Kuzminova, N.V.; Ivankova, A.V.; Ivanov, V.P.; Lozinsky, S.E.; Knyazkova, I.I.; Gavrylyuk, A.O. (World of Medicine and Biology, 2020)
156 patients (65 men and 91 women) with stage II hypertension (stage II EH) were examined. The main group consisted of 124 of them, which according to the daily monitoring of the electrocardiogram had frequent supraventricular (SVPB) (74 persons) or ventricular PB (VPB) (50 persons). The comparison group included 32 patients with stage II EH without arrhythmia. It was established that patients with stage II EH and PB had significantly higher values of systolic (SBP) and diastolic blood pressure (DBP) during the day according to the data of daily blood pressure monitoring (DBPM). In patients with stage II EH, regardless of the presence of arrhythmia, there was a decrease in patients with dipper type and an increase in the number of pathological types of diurnal profile by SBP level, without a significant difference between the groups. In patients with stage II EH with PBs, the daily profile of non-dipper according to the DBP level was more frequent (p = 0.03). The presence of frequent VPB was associated with a predominance of the non-dipper profile in terms of DBT (76.0%, p = 0.0003) compared with patients with SVPB. The data obtained indicate a certain associative link between the disturbance of the diurnal BP profile, mainly DBT and the presence of PBs, namely in patients with stage II EH.